The Economic Consequences Of Mandatory Ifrs Adoption: The Case Of Arab Countries - Bekkaye, Ahmed (University of Eloued جامعة الوادي, 2019)
The study aimed at revealing the nature of the relationship between the economic markets efficiency and the Arab financial reporting environment after converging with IFRS. The paper uses panel cointegration to investigate three main areas: Macroeconomic environment, Goods market efficiency, Market size, by using the Eviews.7 program. Findings: the results showed a long run relationship between the economic markets efficiency and the quality of accounting in Arab countries during the study period. This paper provides new empirical evidence in the context of studying the economic dimensions of IFRS in the Arab economies.
مجلة رؤى المجلد التاسع العدد الأول
Keywords: International accounting convergence; IFRS; Economic Consequences; the economic markets efficiency; Arab countries. Jel Classification Codes: F63; G39; M21; M41; M48; M49